Transitioning from Screen to Scripture: Reclaiming Generation Z through Islamic Education and Moral Development in Indonesian Educational Institutions - Sarinah Sarinah; Abdul Fattah; Maria Ulviani (Universitas Muhammadiyah Malang, 2025)
The emergence of digital culture has profoundly impacted the attitudes, behaviors, and value systems of Generation Z, resulting in a moral disparity between conventional religion doctrines and modern youth experiences. As Indonesian adolescents increasingly engage with screen-based environments, worries grow over the erosion of Islamic character and ethical sensibility. This study examines the critical question of how Islamic Religious Education (PAI) might respond to this moral drift and effectively recapture the spiritual and ethical identity of Generation Z students. The study especially investigates the influence of PAI on the development of Islamic character in students at SMP Unismuh Makassar, while also identifying the principal problems and strategic solutions for its implementation. This qualitative study employs interviews, observations, and documentation as data collection methods. The research participants are PAI educators and students from SMP Unismuh Makassar. The data were evaluated using the steps of reduction, display, and conclusion drawing, with triangulation utilized for validation. The results indicate that PAI plays a crucial role in the internalization of Islamic values, including discipline, honesty, respect, and religious commitment, among pupils. Nonetheless, challenges such as antiquated teaching methods, restricted instructional time, and insufficient incorporation of digital resources impede its effectiveness. The study introduces a hybrid paradigm that integrates classical Islamic education with digital engagement tactics, enhancing its relevance for digitally native learners. In summary, enhancing Islamic Religious Education necessitates pedagogical innovation, the use of educational technology, and improved collaboration among educators, parents, and the school community to facilitate significant character development in the digital age.